Engineering Single‐Atomic Iron‐Catalyst‐Integrated 3D‐Printed Bioscaffolds for Osteosarcoma Destruction with Antibacterial and Bone Defect Regeneration Bioactivity. Issue 31 (19th June 2021) - Wang, Liying; Yang, Qianhao; Huo, Minfeng; Lu, Dan; Gao, Youshui; Chen, Yu; Xu, Huixiong
Abstract: Effective antitumor therapeutics with distinctive bactericidal and osteogenic properties are in high demand for comprehensive osteosarcoma treatment. Here, a "scaffold engineering" strategy that integrates highly active single‐atomic iron catalysts (FeSAC) into a 3D printed bioactive glass (BG) scaffold is reported. Based on the atomically dispersed iron species within the catalysts, the engineered FeSAC displays prominent Fenton catalytic activity to generate toxic hydroxyl radicals (OH) in response to the microenvironment specific to osteosarcoma. In addition, the constructed FeSAC‐BG scaffold can serve as a sophisticated biomaterial platform for efficient osteosarcoma ablation, with concomitant bacterial sterilization via localized hyperthermia‐reinforced nanocatalytic therapeutics. The destruction of the osteosarcoma, as well as the bacterial foci, can be achieved, further preventing susceptible chronic osteomyelitis during osteogenesis. In particular, the engineered FeSAC‐BG scaffold is identified with advances in accelerated osteoconduction and osteoinduction, ultimately contributing to the sophisticated therapeutics and management of osteosarcoma. This work broadens the biomedical potential of single‐atom catalysts and offers a comprehensive clinically feasible strategy for overall osteosarcoma therapeutics, bacterial inhibition, and tissue regeneration. Abstract : Single‐atomic‐catalyst‐engineered 3D scaffolds for osteosarcoma therapy and bone regeneration are reported. A single‐atomic iron catalyst with highly effective hyperthermia‐enhanced catalytic radical generating activities is engineered into a 3D‐printed bioglass scaffold to achieve comprehensive osteosarcoma elimination, antibacterial properties, and bone defect regeneration with biocompatibility.